1, 2, 3-Triazole fused with pyridine/pyrimidine as new template for antimicrobial agents: Regioselective synthesis and identification of potent N-heteroarenes. Issue 20 (1st November 2018) - Marepu, Nagaraju; Yeturu, Sunandamma; Pal, Manojit
Graphical abstract: The 1, 2, 3-triazole fused pyridine/pyrimidine derivatives were synthesized and evaluated as new and potential antimicrobial agents. Highlights: Explored 1, 2, 3-triazolo pyridine/pyrimidine as new template for antimicrobial agents. Demonstrated the application of Buchwald's strategy to N -heteroarene system. Two compounds were comparable to streptomycin and several were comparable to mancozeb. Abstract: The 1, 2, 3-triazole ring fused with pyridine/pyrimidine was explored as new template for the identification of potential antimicrobial agents. The regioselective synthesis of these pre-designed N -heteroarenes was achieved via exploring the application of Buchwald's strategy (i.e. C–N bond formation/reduction/diazotization/cyclization sequence) to the N -heteroarene system. Two of them showed promising antibacterial (comparable to streptomycin) and several showed potent antifungal (comparable to mancozeb) activities.